Smac mimetics LCL161 and GDC-0152 inhibit osteosarcoma growth and metastasis in mice - Tanmay M. Shekhar (BMC Cancer, 2019)
Abstract Background Current therapies fail to cure over a third of osteosarcoma patients and around three quarters of those with metastatic disease. “Smac mimetics” (also known as “IAP antagonists”) are a new class of anti-cancer agents. Previous work revealed that cells from murine osteosarcomas were efficiently sensitized by physiologically achievable concentrations of some Smac mimetics (including GDC-0152 and LCL161) to killing by the inflammatory cytokine TNFα in vitro, but survived exposure to Smac mimetics as sole agents. Methods Nude mice were subcutaneously or intramuscularly implanted with luciferase-expressing murine 1029H or human KRIB osteosarcoma cells. The impacts of treatment with GDC-0152, LCL161 and/or doxorubicin were assessed by caliper measurements, bioluminescence, 18FDG-PET and MRI imaging, and by weighing resected tumors at the experimental endpoint. Metastatic burden was examined by quantitative PCR, through amplification of a region of the luciferase gene from lung DNA. ATP levels in treated and untreated osteosarcoma cells were compared to assess in vitro sensitivity. Immunophenotyping of cells within treated and untreated tumors was performed by flow cytometry, and TNFα levels in blood and tumors were measured using cytokine bead arrays. Results Treatment with GDC-0152 or LCL161 suppressed the growth of subcutaneously or intramuscularly implanted osteosarcomas. In both models, co-treatment with doxorubicin and Smac mimetics impeded average osteosarcoma growth to a greater extent than either drug alone, although these differences were not statistically significant. Co-treatments were also more toxic. Co-treatment with LCL161 and doxorubicin was particularly effective in the KRIB intramuscular model, impeding primary tumor growth and delaying or preventing metastasis. Although the Smac mimetics were effective in vivo, in vitro they only efficiently killed osteosarcoma cells when TNFα was supplied. Implanted tumors contained high levels of TNFα, produced by infiltrating immune cells. Spontaneous osteosarcomas that arose in genetically-engineered immunocompetent mice also contained abundant TNFα. Conclusions These data imply that Smac mimetics can cooperate with TNFα secreted by tumor-associated immune cells to kill osteosarcoma cells in vivo. Smac mimetics may therefore benefit osteosarcoma patients whose tumors contain Smac mimetic-responsive cancer cells and TNFα-producing infiltrating cells.